Hindu laws (New Delhi, 2014)
Book consists of these topics 1st Choice of Bench & Bar- Accurate and up-to-date Incorporating latest amendments Beautifully printed on superior quality paper Reasonably priced Along with: - Important Case Law in short comments form - Introduction - Statement of Objects & Reasons - List of Amending Acts - Relevant State Amendments - Detailed footnotes for historical legislative effect
Keywords: Hindu laws-India